BIMTEK PENYUSUNAN PERANGKAT PEMBELAJARAN BERORIENTASI LITERASI TANGGAP BENCANA - Abdurrahman Abdurrahman; Feriansyah Sesunan; Hervin Maulina; Novinta Nurulsari (Universitas Sanata Dharma, 2021)
Educating residents around the coastal areas not only involves the central and regional governments, but also all aspects of the community structure. Considering the number of children who are victims of disasters and the lack of integration of disaster response literacy in the field of education, University of Lampung, in this case the Faculty of Teacher Training and Education (FKIP) also participated in educating residents around the coast, especially the South Lampung area, through the field of Education. In addition, based on the results of direct interviews with one of the Sciences Teachers of Primary School in South Lampung, it is known that the unavailability of teaching materials that build disaster response literacy and the weakness of teachers' skills in developing integrated lesson plan for disaster response. Therefore, there was a Technical Guidance (Bimtek) activity for the preparation of lesson plan oriented towards disaster response literacy of junior high school students for science teachers. Through this Bimtek, science teachers are equipped with knowledge about integrating disaster response into learning through lesson plan and learning media.